INTEGRATED FLASHCARD AND LUDO VOCABULARY LEARNING GAME TO INCREASE VOCABULARY ACHIEVEMENT OF THE FIRST GRADE OF JUNIOR HIGH SCHOOL: RESEARCH AND DEVELOPMENT - Endang Badriyatin. F; Supriyono; Miza Rahmatika Aini (Universitas Islam Balitar, 2022)
This research was aimed to establish, to find out the effectiveness, and to know the teacher’s and student’s responses of Flash Ludo Game as a vocabulary learning media for first grade students of Junior High School. The researcher was applied Research and Development (R&D) design whis is adapted from Sugiyono. It consisted of five phases, they were: data collection and finding potentials and problems, design and development, expert validation and revision, product trial, and final product. The final product of the model consisted of three kinds of flashcards, a set of ludo game, and three kinds of guidebooks. The result of design and development showed that the model was very valid, the average of material and media experts was 92.5%. The product trial was done with 20 seventh grade students as participants. The one-group pre-post test showed that before using the model, the average student’s score was (45.80) and after using the model, it reached (84.05). From the t-test analysis, the researcher found that the sig (2.tailed) value was .000, it showed that the Sig. value (2-tailed) <0.05, in means that was a significant difference between pre-test and post-test. The result of teacher’s and student’s responses showed that the model was very proper, with the average result was 94%. The vocabulary learning media was effective and improve student’s vocabulary achievement for the first grade students of Junior High School.